Problems in the installation and maintenance of water supply piping system in government office building / Umi Kalsom Ahmad - Ahmad, Umi Kalsom (Faculty of Architecture, Planning and Surveying, 2013)
Over the decades, problems in the installation and maintenance still occurred even there is maintenance staff in every commercial building. Maintenance staff in every department plays an importance role in sustain and maintain the building services system include water supply piping system apply in the building. However Malaysia, as a developing country are still premature to faces some staff that lack or aware of their working scope. This situation has lead many problems occurred in the major scope of building services and minor scope of water supply piping system in government office building. Thus, to identify problem in the installation and maintenance of water supply piping system, this research aims to analyze the determinant problem, types and best opinion on ways to reduce the problem that has been analyze and determine from this research findings. Questionnaire was then developed in targeting maintenance staff as sampling of this research. Set of questionnaire then distributed to all maintenance staff in the building management unit in the selected three case studies. There are not many staff in each building. Three staff in Post Office building, 6 staff in Selangor Secretariat building (SUK) and 3 staff in IPD Shah Alam as IPD Shah Alam building mostly use contractor expertise in maintenance work due to embedded piping system in wall. The data was analyzed using bar graph and line graph.